Representation of an Elderly Person in Polish Social Campaigns. A Case Study - Kosman, Marcin (Papers in Linguistics, 2024)
The article discusses the portrayal of the elderly in social campaigns, specifically in the campaign of the Polish Ministry of Digital Affairs. As most of the existing studies have focused on advertising, there is a research gap concerning the representation of the elderly in social campaigns that the present paper aims to fill. Combining insights based on critical discourse analysis and social semiotics, the study is grounded in multimodal discourse analysis, which allows one to perform a thorough investigation of various modes to determine how they form a coherent meaning. Overall, the portrayal of the elderly person was positive as they were shown as active and independent users of the Internet, which differs from the traditional representation of such people. Encouraging the audience to emulate the actions and behaviour of the protagonist appears to be a good solution regarding middle- and upper-class senior citizens as they have both social and financial capital to act like Barbara Bursztynowicz, who appears in the campaign. However, this might not be as effective regarding people who are digitally excluded. The discussed campaign successfully challenges stereotypical views on old age (i.e. senior citizens not being able to use modern technologies, or being dependent on younger family members), offering a different and positive perspective by emphasizing the agency of senior citizens.